Impact of antiglaucoma drug number and class on corneal epithelial thickness measured by OCT - Miklaszewski, Piotr; Gadamer, Anna Maria; Janiszewska-Bil, Dominika; Lyssek-Boroń, Anita; Dobrowolski, Dariusz; Wylęgała, Edward; Grabarek, Beniamin Oskar; Koss, Michael Janusz; Krysik, Katarzyna (Pharmaceuticals, 2025)
Background/Objectives: The corneal epithelium plays a vital role in maintaining corneal transparency and ocular surface integrity. Chronic topical use of antiglaucoma medications may induce epithelial changes, especially with the concurrent use of multiple agents. This study aimed to evaluate the association between the number and class of antiglaucoma medications and central corneal epithelial thickness (CET), measured using a spectral-domain optical coherence tomography (SD-OCT) device. - Methods: This cross-sectional study included 456 eyes from 242 adults (median age 72 years), grouped by the number of antiglaucoma agents used (0–4 medications). All pharmacologically treated participants had received the same regimen for ≥6 months. CET was measured using SD-OCT (SOLIX, Optovue). Generalized estimating equations (GEEs) accounted for inter-eye correlation. Two models were constructed: one evaluating specific medication effects and another assessing CET reduction per additional drug used. Age and sex were included as covariates. - Results: CET progressively decreased with the number of medications, ranging from 53 µm in controls to 48 µm with quadruple therapy. Multivariable GEE analysis confirmed a cumulative thinning effect, with each additional medication associated with further CET reduction (β = −2.83 to −9.17 µm, p < 0.001). Latanoprost exerted the most pronounced single-drug effect (β = −3.01 µm, p < 0.001). Age was a modest negative predictor, while sex showed no significant effect. - Conclusions: The cumulative number and specific class of antiglaucoma medications have a significant impact on corneal epithelial thickness. These results emphasize the need for vigilant ocular surface evaluation in patients on multi-drug regimens and propose CET as a surrogate marker for the burden of topical therapy.